Respuesta :
For the answer to the question above, I'll show my to solution to the answer below.
average rate of change is
(f(5) - f(1))/(5 - 1) =
(17 - 5^2 - (17 - 1^2))/4 =
(17 - 25 - 17 + 1)/4 =
So the answer for this problem is
-6
I hope my answer helped you. Feel free to ask for more questions.
average rate of change is
(f(5) - f(1))/(5 - 1) =
(17 - 5^2 - (17 - 1^2))/4 =
(17 - 25 - 17 + 1)/4 =
So the answer for this problem is
-6
I hope my answer helped you. Feel free to ask for more questions.
Answer:A
Step-by-step explanation:
(f(5) - f(1))/(5 - 1) =
(17 - 5^2 - (17 - 1^2))/4 =
(17 - 25 - 17 + 1)/4 = 6